Construction, Surveying and Civil Engineering - Gorse, Christopher A. ; Johnston, David, 1971- and Pritchard, Martin (Oxford Oxford University Press, 2012)
This new dictionary is the most up-to-date A to Z of construction, surveying, and civil engineering terms and definitions available. Covering all core aspects of construction and related areas, it provides a one-stop reference for construction students and professionals
Keywords: Surveying -- Building